69.1k views
2 votes
Given the equation 7(x + 2) = 2x − 1, solve for the variable. Explain each step and justify your process. Jeff solved a similar equation below. Is Jeff's solution correct? Explain why or why not. 3x − 2 = 5(x + 2) 3x − 2 = 5x + 10 8x = 8 x = 1

1 Answer

4 votes
You have to distribute the 7 to x and 2 so :
7x+14=2x-1
Add one to both sides (inverse operations)
7x+14=2x-1
+1 +1
7x+15=2x
Cross Cancel by subtracting 7x from both sides
7x+15=2x
-7x -7x
15=-5x
Divide by -5
15/-5= -5/-5
X= -3

User Gyscos
by
5.7k points